Can urban metabolism models advance green infrastructure planning? Insights from ecosystem services research. (May 2020) - Perrotti, Daniela; Stremke, Sven
Urban metabolism studies have gained momentum in recent years as a means to assess the environmental performance of cities and to point to more resource-efficient strategies for urban development. Recent literature reviews report a growing number of applications of the industrial ecology model for material flow analysis in the design of the built environment. However, applications of material flow analysis in green infrastructure development are scarce. In this article, we argue that: (i) the use of material flow analysis in green infrastructure practice can inform decision-making towards more resource-efficient urban planning; (ii) the ecosystem service concept is critical to operationalize material flow analysis for green infrastructure planning and design, and, through this, can enhance the impact of urban metabolism research on policy making and planning practice. The article draws from a systematic review of literature on urban ecosystem services and benefits provided by green infrastructure in urban regions. The review focuses on ecosystem services that can contribute to a more energy-efficient and less carbon-intensive urban metabolism. Using the Common International Classification of Ecosystem Services as a baseline, we then discuss opportunities for integrating energy provision and climate regulation ecosystem services in material flow analysis. Our discussion demonstrates that the accounting of ecosystem services in material flow analysis enables expressing impacts of green infrastructure on the urban energy mix (renewable energy provision), the magnitude of energy use (mitigation of building energy demand) and the dynamics of biogeochemical processes in cities (carbon sequestration). We finally propose an expanded model for material flow analysis that illustrates a way forward to integrate the ecosystem service concept in urban metabolism models and to enable their application in green infrastructure planning and design.